2019
DOI: 10.1002/ijgo.13075
|View full text |Cite
|
Sign up to set email alerts
|

Components of obstetric violence in health facilities in Quito, Ecuador: A descriptive study on information, accompaniment, and position during childbirth

Abstract: Objective: To describe three factors of obstetric violence in health centers that attend births in Quito, Ecuador: information; accompaniment; and free position. Method:A cross-sectional descriptive study of 388 women was conducted, focusing on the analysis of three factors of obstetric violence. This study forms part of a larger study that explores the experiences of women in childbirth in Quito between July 1, 2016 and July 1, 2017.Results: Of all procedures, the performance of episiotomies and the applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
1
10
0
4
Order By: Relevance
“…Studies on vBI have found that it is a frequently used procedure although there is no evidence of its benefit. Instead, it carries high vBI potential and the WHO recommendations strongly discourage it due to its potential for harm ( 11 , 37 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on vBI have found that it is a frequently used procedure although there is no evidence of its benefit. Instead, it carries high vBI potential and the WHO recommendations strongly discourage it due to its potential for harm ( 11 , 37 39 ).…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 The high number of obstetric violence in the country constitutes a serious public health subject that implies individual consequences in the short and long term, these are not only physical but also psychological and social. 8 , 10…”
Section: Introductionmentioning
confidence: 99%
“…7 In Ecuador, there are demonstrations of obstetric violence in public and private health units, including indiscriminate vaginal touching, caesarean sections without medical reason, routine episiotomies, separation of the newborn from his mother, not offering help to start maternal breastfeeding, among others. 8,9 The high number of obstetric violence in the country constitutes a serious public health subject that implies individual consequences in the short and long term, these are not only physical but also psychological and social. 8,10 In an investigation in Quito 9 where it was reported that 120 women who gave birth for the first time, 62 (51.7%) had an episiotomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies identify that approximately 30% of childbirth experiences can be considered traumatic and/or as having OV components [5,6]. Moreover, OV can be found around the world in all continents: America [7][8][9], Africa [10][11][12], Asia [13], Europe [6,14,15] and Australia [16,17]. These negative experiences and the presence or practice of OV have consequences for the woman and her newborn, for society and for the health professionals who observe or practice it.…”
Section: Introductionmentioning
confidence: 99%